2023
DOI: 10.3390/plants12071422
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Essential Oil Quantity and Quality of Thyme (Thymus vulgaris L.) by Integrative Application of Chitosan Nanoparticles and Arbuscular Mycorrhizal Fungi under Water Stress Conditions

Abstract: Water stress is one of the critical abiotic stresses and limiting factors in the productivity of plants, especially in arid and semi-arid regions. In recent years, the application of bio-fertilizer and stress-modulating nanoparticles (NPs) is known as one of the eco-friendly strategies for improving plants quantity and quality under stressful conditions. In order to achieve the desirable essential oil (EO) quality and quantity of thyme in water deficit conditions, a 2-year field experiment was carried out as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Biotic factors, including the application of bio-fertilizers and stress-modulating nanoparticles, significantly influence the composition of thyme essential oil. Amani Machiani et al [119] demonstrated that the use of arbuscular mycorrhizal fungi (AMF) and chitosan nanoparticles (CHT) as bio-fertilizers, either individually or in combination, enhances both the quantity and quality of thyme essential oil, particularly thymol, p-cymene, and γ-terpinene. Furthermore, the application of Thiobacillus bio-fertilizer and treatment with superabsorbent were found to impact the content of thymol, caryophyllene, and borneol in Thymus vulgaris and T. daenesis [120].…”
Section: Effect Of Biofertilizersmentioning
confidence: 99%
See 1 more Smart Citation
“…Biotic factors, including the application of bio-fertilizers and stress-modulating nanoparticles, significantly influence the composition of thyme essential oil. Amani Machiani et al [119] demonstrated that the use of arbuscular mycorrhizal fungi (AMF) and chitosan nanoparticles (CHT) as bio-fertilizers, either individually or in combination, enhances both the quantity and quality of thyme essential oil, particularly thymol, p-cymene, and γ-terpinene. Furthermore, the application of Thiobacillus bio-fertilizer and treatment with superabsorbent were found to impact the content of thymol, caryophyllene, and borneol in Thymus vulgaris and T. daenesis [120].…”
Section: Effect Of Biofertilizersmentioning
confidence: 99%
“…The composition of thyme essential oil is highly influenced by a variety of factors, as discussed previously and summarized in Table 2, showing the effect of different abiotic and biotic factors on essential oil composition of thyme species. Under the different mentioned factors, Thymus vulgaris shows an increased rate of thymol in the essential oil, in case of increased salinity at 150 mM NaCl [125] and at 100 mM NaCl [126] using substrate that contain 100 gm −2 of humic acid, using biofertilizers such as AMF [119] or PGPB [121], and in the case of increasing shade rate by using shade nets with a shade index of 40% [127]. However, thymol rate decreased in case of drought stress [102,103].…”
Section: Effect Of Plant Densitymentioning
confidence: 99%